Three new species of the Synapturanus rabus complex (Microhylidae: Otophryninae) in Colombia with a review of the genus Synapturanus - Osorno-Muñoz, Mariela; Gutiérrez-Lamus, Doris L.; Lynch, John; Keeffe, Rachel; Caicedo-Portilla, José Rancés; Chan, Kin Nok; Tonini, João F. R.; de Sá, Rafael O. (Zootaxa, 2023)
The Neotropical microhylid genus Synapturanus was represented by only three species for almost five decades and remains poorly known. Recently two new species were described from the Eastern Guyana Shield, one from Peru, and one from Brazil. We describe three new species related to the S. rabus species complex with known distribution only in western Amazonia, Colombia. The S. rabus complex consists of the smallest species in the genus; one of the new species is slightly larger than S. rabus and we describe its full osteology; the other two new species are smaller than S. rabus. We also described the call and larvae of one of the new species. We provide an updated diagnosis and review the available molecular and phenotypic data for the genus.